Recruitment of TRIM33 to cell‐context specific PML nuclear bodies regulates nodal signaling in mESCs. (16th December 2022) - Sun, Hongyao; Chen, Yutong; Yan, Kun; Shao, Yanqiu; Zhang, Qiangfeng C; Lin, Yi; Xi, Qiaoran
Abstract: TRIM33 is a chromatin reader required for mammalian mesendoderm differentiation after activation of Nodal signaling, while its role in mESCs is still elusive. Here, we report that TRIM33 co‐localizes with promyelocytic leukemia nuclear bodies (PML‐NBs) specifically in mESCs, to mediate Nodal signaling‐directed transcription of Lefty1/2. We show that TRIM33 puncta formation in mESCs depends on PML and on specific assembly of PML‐NBs. Moreover, TRIM33 and PML co‐regulate Lefty1 / 2 expression in mESCs, with both PML protein and formation of mESCs‐specific PML‐NBs being required for TRIM33 recruitment to these loci, and PML‐NBs directly associating with the Lefty1 / 2 loci. Finally, a TurboID proximity‐labeling experiment confirmed that TRIM33 is highly enriched only in mESCs‐specific PML‐NBs. Thus, our study supports a model in which TRIM33 condensates regulate Nodal signaling‐directed transcription in mESCs and shows that PML‐NBs can recruit distinct sets of client proteins in a cell‐context‐dependent manner. Synopsis: The chromatin reader TRIM33 is involved in cell fate decisions under different cell contexts, but the molecular details are still elusive. Here, TRIM33 is found to co‐condense with PML nuclear bodies (PML‐NBs) in mESCs to transcriptionally regulate Lefty1/2 expression upon Nodal signaling. TRIM33 is recruited into PML‐NBs selectively in mESCs, but not in differentiated cells. PML‐NB client protein composition differs between mESCs, oxidative stress‐treated mESCs, and differentiated cells. PML‐NBs regulate expression of gene clusters, including Lefty1/2 loci in mESCs. PML‐NBs form a regulatory hub for TRIM33 control of Lefty1/2 expression upon Nodal signaling. Abstract : mESC‐specific PML‐NBs including TRIM33 bind to Lefty1/2 loci and regulate gene cluster expression.